Restricted nutrient intake does not alter serum-mediated measures of implant response in cell culture - Reinhardt, Christopher D.; Lee, Tiffany L.; Thomson, Daniel U.; Mamedova, Laman K.; Bradford, Barry J. (My University, 2014)
Background: During nutritional stress, reduced intake may reduce the efficacy of anabolic implants. This study was conducted to evaluate basic cellular responses to a growth promotant implant at two intake levels. Methods: Sixteen crossbred steers (293 ± 19.3 kg) were used to evaluate the impact of anabolic implants in either an adequate or a restricted nutritional state. Steers were trained to individual Calan gates, and then randomly assigned to 1 of 4 treatments in a 2 × 2 factorial arrangement. Treatments consisted of: presence or absence of an anabolic growth implant (Revalor-XS, 200 mg TBA and 40 mg estradiol; IMPLANT or CONTROL) and a moderate energy, pelleted, starting cattle diet fed at either 2.0 × or 1.0 × maintenance energy (NEM) requirements (HIGH or LOW). Serum (d 0, 14, and 28) was used for application to bovine muscle satellite cells. After treatment with the serum (20% of total media) from the trial cattle, the satellite cells were incubated for 72 h. Protein abundance of myosin heavy chain (MHC), phosphorylated extracellular signal-related kinase (phospho-ERK), and phosphorylated mammalian target of rapamycin (phospho-mTOR) were analyzed to determine the effects of implant, intake, and their interaction (applied via the serum). Results: Intake had no effect on MHC (P = 0.85) but IMPLANT increased (P < 0.01) MHC abundance vs. CONTROL. Implant status, intake status, and the interaction had no effect on the abundance of phospho-ERK (P ≥ 0.23). Implanting increased phospho-mTOR (P < 0.01) but there was no effect (P ≥ 0.51) of intake or intake × implant. Conclusions: The nearly complete lack of interaction between implant and nutritional status indicates that the signaling molecules measured herein respond to implants and nutritional status independently. Furthermore, results suggest that the muscle hypertrophic effects of anabolic implants may not be mediated by circulating IGF-1.
Keywords: Beef cattle; Implant; Muscle; Myosin heavy chain; Nutrient restriction; Satellite cells